2021
DOI: 10.1021/acsomega.1c05030
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Allomelanin from Pathogenic Black Knot Fungus─a Sustainable Source of Melanin

Abstract: Melanin, a widespread pigment found in many taxa, is widely recognized for its high refractive index, ultraviolet (UV) protection, radical quenching ability, metal binding, and many other unique properties. The aforementioned characteristic traits make melanin a potential candidate for biomedical, separation, structural coloration, and space applications. However, the commercially available natural (sepia) and synthetic melanin are very expensive, limiting their use in various applications. Additionally, eumel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 59 publications
(256 reference statements)
1
7
0
Order By: Relevance
“…but the pigment was found to be irregular in shape size by SEM, and it is likely this was probably destroyed by repeated acid–base extraction. Similarly, Singla et al 62 observed that allomelanin extracted from pathogenic black knot fungus was disrupted and showed irregular morphology, and it was uncertain whether this structure was present in the pathogenic bacteria. The extraction method of neuromelanin is complicated because it requires the isolation of melanin granules from brain cells.…”
Section: Extraction Methods Of Melaninmentioning
confidence: 99%
See 3 more Smart Citations
“…but the pigment was found to be irregular in shape size by SEM, and it is likely this was probably destroyed by repeated acid–base extraction. Similarly, Singla et al 62 observed that allomelanin extracted from pathogenic black knot fungus was disrupted and showed irregular morphology, and it was uncertain whether this structure was present in the pathogenic bacteria. The extraction method of neuromelanin is complicated because it requires the isolation of melanin granules from brain cells.…”
Section: Extraction Methods Of Melaninmentioning
confidence: 99%
“…62 Allomelanin from pathogenic black knot fungus has two absorption peaks: the peak at 1381 cm À1 is associated with the aromatic C-C linear stretching or C-N stretching of the indole structure, while the peak at 1593 cm À1 is attributed to the CQC bond of the indole structure. 62 The allomelanin of C. islandica had a distinct peak in the range of 1020 cm À1 associated with the stretching vibration of the (C-O-C) group; no absorption was recorded at 1720 cm À1 , which may indicate the absence of free carboxyl groups. 61 Pyomelanin was found with a broad absorption in the 3300-3420 cm À1 range, which corresponds to the stretching vibrations of -NH and -OH.…”
Section: Structure Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The alkali hydrolytic treatment, on the other hand, is based on the soluble nature of melanin in the alkali. The melanized tissue is first solubilized in the alkali, followed by melanin precipitation using acid, which is normally repeated several times for complete melanin precipitation. , This method results in irregular melanin aggregates that can be contaminated by sulfur from the hydrolysis of sulfur-containing amino acids, particularly for those keratinous sources (e.g., hairs) . On the other hand, enzymatic digestion method is a milder alternative that produces intact melanin granules that are morphologically and chemically unchanged .…”
Section: Syntheses and Structures Of Melaninmentioning
confidence: 99%